1987
DOI: 10.1136/adc.62.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular leucomalacia and neurodevelopmental outcome in preterm infants.

Abstract: SUMMARY During an 18 month period, 120 preterm infants of 34 weeks' gestation or less were prospectively examined for periventricular leucomalacia (PVL) by cerebral ultrasound. Neurological and developmental assessment was carried out at 18 months of age corrected for prematurity in 82 surviving neonates. The developmental outcome (Griffiths development quotient) was above 80 and similar in infants with normal scans (n=41), isolated periventricularintraventricular haemorrhage (n=13), and post-haemorrhagic hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1
4

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 22 publications
8
57
1
4
Order By: Relevance
“…It is also apparent that discrete involvement of a single zone only is not associated with adverse outcome. These findings are largely in agreement with those of FAWER et al [8] who reported the outcome of 26 survivors with PVL and those of Cooke [4] who found that the presence of cystic lesions, particularly when bilateral, were strongly predictive of developmental delay. In general, the more mature infants who developed CPVL had the worst outcome.…”
Section: Outcomesupporting
confidence: 91%
See 2 more Smart Citations
“…It is also apparent that discrete involvement of a single zone only is not associated with adverse outcome. These findings are largely in agreement with those of FAWER et al [8] who reported the outcome of 26 survivors with PVL and those of Cooke [4] who found that the presence of cystic lesions, particularly when bilateral, were strongly predictive of developmental delay. In general, the more mature infants who developed CPVL had the worst outcome.…”
Section: Outcomesupporting
confidence: 91%
“…Cyst size has been previously shown to be an accurate predictor of the extent of the neurological damage [8,10] and we have confirmed this finding. In 11 infants the largest cyst was less than 1 cm in diameter and eight (73%) of these infants had no evidence of cerebral palsy.…”
Section: Outcomesupporting
confidence: 88%
See 1 more Smart Citation
“…The follow-up examination consisted of a neurological ex amination [20], an assessment of development using Griffith's [21] scale and an evaluation of vision and hearing according to Sheridan [22,23]. Auditory brainstem response (ABR) and cerebral ultrasound were performed with conventional techniques [5,7,[24][25][26][27][28], In our unit, ABR testings were performed before discharge in all infants who had one or more of the following risk factors: congenital malformations, congenital familial deafness, birth weight < 1,000 g. hypcrbilirubinaemia with exchange transfusion, con genital infections, prolonged acidosis (arterial or capil lary pH < 7.2 lasting more than 2 h). neonatal seizures, meningitis, prolonged aminoglycoside therapy and high peak or trough concentrations of aminoglyco sides.…”
Section: Methodsmentioning
confidence: 99%
“…Some children recover completely, whereas others suffer from severe handicapping conditions (Costello et al, 1988;Ford et al, 1989 (Volpe, 1995). In preterm infants, it has been reported that frontally located lesions are associated with better outcomes than lesions located parietally or occipitally (Fawer et al, 1987;Fazzi et al, 1994).…”
Section: Ngst and Motor Development After Brain Lesion At Early Agementioning
confidence: 99%